Focal Mechanisms of Deep Low‐Frequency Earthquakes Beneath Zao Volcano, Northeast Japan, and Relationship to the 2011 Tohoku Earthquake. Issue 13 (8th July 2019) - Oikawa, Genki; Aso, Naofumi; Nakajima, Junichi
Abstract: Small, deep low‐frequency earthquakes (LFEs) with dominant frequencies of 2–8 Hz occur at depths of 20–40 km and are thought to be related to movement of magma or crustal fluid, but their physical source processes remain largely unknown. Therefore, we determine the focal mechanisms of LFEs beneath Zao volcano, Northeast Japan, using the S / P amplitude ratio. Most focal mechanisms are classified into five groups: three types of double couples, a compensated linear vector dipole group, and a single force group. Double couples in 2007–2012 are consistent with those expected for the regional stress field, but no such events have been observed since 2013. This transition in focal mechanisms was simultaneous with a rapid increase in LFE activity beneath Zao. Our results suggest that LFEs beneath Zao were controlled mainly by the local stress field, but the stress field changed about two years after the 2011 Tohoku earthquake. Plain Language Summary: Low‐frequency earthquakes are small events caused by slow deformation in the Earth. However, the source process of low‐frequency earthquakes at volcanoes is poorly understood because there are relatively few observations. We determined focal mechanisms of several low‐frequency earthquakes beneath Zao volcano, Japan. Focal mechanisms changed two years after the Tohoku earthquake, coincident with a rapid increase in activity. We suggest that the Tohoku earthquake influenced the stress field at the volcanic front after a two‐year delay, resulting in this transition. Key Points: Mechanisms of low‐frequency earthquakes beneath Zao volcano are classified into five groups The only group that predates the Tohoku earthquake has a double‐couple mechanism consistent with the local stress field Mechanisms vary with stress changes related to the Tohoku earthquake